Induction of Heme Oxygenase-1 Inhibits Monocyte Chemoattractant Protein-1 mRNA Expression in U937 Cells - Shokawa, Tomoki; Yoshizumi, Masao; Yamamoto, Hideya; Omura, Shinji; Toyofuku, Mamoru; Shimizu, Yoshito; Imazu, Michinori; Kohno, Nobuoki (Journal of Pharmacological Sciences, 2006)
Heme oxygenase-1 (HO-1) is a stress-inducible isoform of HO with potential cytoprotective effects. Monocyte activation/migration mediated by monocyte chemoattractant protein-1(MCP-1) is one of the earliest and important events in the pathogenesis of atherosclerosis. We examined the effect of HO-1 on the production of lysophosphatidylcholine (Lyso-PC)-induced MCP-1 in the human promonocytic cell line U937. Increased HO-1 induction by hemin resulted in a significant decrease in the Lyso-PC-mediated induction of MCP-1 mRNA expression. SnPP (IX), the specific inhibitor of HO-1 enzymatic activity, prevented the hemin-mediated attenuation of MCP-1 mRNA expression. These results suggest that HO-1 may work as an anti-atherogenic agent through the attenuation of MCP-1 production.